Framing the Iran-Israel Conflict: Ideological Representation in Al-Jazeera’s Nuclear News - Roziki, Khafid; Faisol, M; Hidayat, D; Sutaman, Sutaman (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study applies discourse analysis to examine how Al-Jazeera portrays Iran's nuclear program, highlighting its language choices, narrative strategies, and ideological frameworks. The results show that Al-Jazeera forms a defensive narrative for Iran, emphasizing the threat from Israel while downplaying the image of Iran's nuclear ambitions. In its reporting, Al-Jazeera strategically uses terms such as "deterrence," "threshold capability," and "fatwa limits" to portray Iran as a country that acts within its limits and only responds to external pressure, not as an aggressor. In addition, this study also highlights the dynamics of global escalation, especially how Russia and the United States play a role in influencing Israeli policy. Russia's warnings against attacks on Iran's nuclear facilities and US diplomatic interventions show how global powers shape strategic calculations in regional security. In terms of ideology, Al-Jazeera's reporting reflects three main themes: support for Iran's nuclear strategy within the framework of state sovereignty, rejection of Western dominance, and criticism of US influence in Israeli policy. This editorial stance shows Al-Jazeera's tendency to challenge Western narratives and support multipolar geopolitical discourse. This study contributes to the study of media discourse by highlighting how language choices and visual elements in news reporting can shape geopolitical perceptions. By analyzing Al-Jazeera’s coverage, this study highlights the media’s role in constructing competing realities in international conflicts, while also offering insights into the relationship between journalism, ideology, and strategic communication in Middle Eastern mediaKeywords: ideological representation, iran-israel conflict, nuclear news, stuart hall, al-jazeera